1971
DOI: 10.1161/01.res.29.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and interstitial Pulmonary Edema in the Dog

Abstract: Histamine, administered to dogs by various routes, produced peribronchial interstitial edema. Using colloidal carbon as an electron-dense tracer, it was shown that bronchial venules had become leaky at the same time that the minute blood vessels of the pulmonary circulation remained unaffected by the histamine. The effect of histamine was rapid and brief in duration: wide interendothelial gaps appeared in the walls of bronchial venules through which blood and tracer escaped into the interstitium. This action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

1975
1975
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(49 citation statements)
references
References 30 publications
2
46
0
1
Order By: Relevance
“…There was no difference between the steady- Histamine has also been shown to increase microvascular permeability in the lung. Pietra et al demonstrated leakage of carbon particles from bronchial venules caused by histamine in dogs (14). We previously reported large, sustained increases in lung lymph flow and lymph protein clearance caused by histamine I____.____.____ t__ infusion in unanesthetized sheep (1).…”
Section: Resultsmentioning
confidence: 90%
“…There was no difference between the steady- Histamine has also been shown to increase microvascular permeability in the lung. Pietra et al demonstrated leakage of carbon particles from bronchial venules caused by histamine in dogs (14). We previously reported large, sustained increases in lung lymph flow and lymph protein clearance caused by histamine I____.____.____ t__ infusion in unanesthetized sheep (1).…”
Section: Resultsmentioning
confidence: 90%
“…Известно, что высокие концентрации гистамина приводят к повышению проницаемости легочных ка пилляров [25] и бронхиальных венул, увеличивая поры их эндотелия [26]. Он также вызывает сужение перифе лабораторных показателей у больных с осложненным течением заболевания (n=22) рических бронхов [27], способствуя нарушению венти ляционной функции легких и создавая предпосылки для развития в них воспалительных процессов.…”
Section: клинические критерииunclassified
“…Only 150 mg/kg increased leakage and was therefore chosen as the most effective dose. [14][15][16][17][18][19][20]. None of the doses tested altered leakage in the parenchyma.…”
Section: Development Of a Bronchial Microvascular Leakage Modelmentioning
confidence: 99%
“…10 Inflammatory mediators have previously been shown to cause the formation of gaps up to 500 nm between bronchial endothelial cells. 18,19 We, therefore, developed a model of bronchial microvascular leakage using the inflammatory mediators PAF, histamine and bradykinin, in an attempt to open the gaps between the bronchial endothelial cells and allow more LPD complexes to escape from the bronchial vasculature. Although the combined optimized doses of PAF and histamine significantly increased leakage in the larynx/trachea and main bronchi, the mediators did not increase LPD escape from the bronchial vasculature.…”
Section: IV Delivery Of Lpdmentioning
confidence: 99%
See 1 more Smart Citation